Efficacy and safety of MYL‐1501D versus insulin glargine in people with type 1 diabetes mellitus: Results of the INSTRIDE 3 phase 3 switch study. Issue 3 (4th December 2019) - Blevins, Thomas C.; Barve, Abhijit; Raiter, Yaron; Aubonnet, Patrick; Athalye, Sandeep; Sun, Bin; Muniz, Rafael
Abstract: Aims: To assess the efficacy, insulin dose, safety and immunogenicity when people with type 1 diabetes mellitus switched between MYL‐1501D and reference insulin glargine (Lantus®; Sanofi‐Aventis US LLC, Bridgewater, New Jersey). Materials and methods: Eligible participants from INSTRIDE 1 who completed 52 weeks of reference insulin glargine treatment were randomized 1:1 to the reference sequence (n = 63; reference insulin glargine for 36 weeks) or to the treatment‐switching sequence (n = 64; MYL‐1501D [weeks 0–12], reference insulin glargine [weeks 12–24] and MYL‐1501D [weeks 24–36]). Change in glycated haemoglobin (HbA1c) from baseline to week 36 was the primary efficacy endpoint used to demonstrate equivalence between the two treatment sequences. Secondary endpoints included: change in fasting plasma glucose (FPG), self‐monitored blood glucose (SMBG) and insulin dose; immunogenicity; and adverse events, including hypoglycaemia. Results: Mean changes in HbA1c (least squares [LS] mean [SE]) from baseline to week 36 were −0.05 (0.032) and −0.06 (0.034) for the treatment‐switching and reference sequences, respectively (LS mean difference 0.01 [95% CI −0.085 to 0.101]). Treatment sequences were comparable in terms of secondary endpoints, including FPG, SMBG and insulin dose, and the safety and immunogenicity profiles of the two sequences were similar. Conclusions: Switching participants between MYL‐1501D and reference insulin glargine demonstrated equivalent efficacy and similar safety and immunogenicity, showing that people taking reference insulin glargine can safely switch to MYL‐1501D.